2006
DOI: 10.1103/physreve.73.036302
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the transverse magnetization of rotating ferrofluids

Abstract: We report on measurements of the transverse magnetization of a ferrofluid rotating as a rigid body in a constant magnetic field, H0, applied perpendicular to the axis of rotation. The rotation of the fluid leads to a nonequilibrium situation, where the ferrofluid magnetization M and the magnetic field within the sample, H, are no longer parallel to each other. The off-axis magnetization perpendicular to H0 is measured as a function of both the applied magnetic field H0 and the angular frequency Omega. The latt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 19 publications
2
44
0
Order By: Relevance
“…For magnetite based particles, such as used here, this critical magnetic core diameter is around 20 nm, though as demonstrated in Ref. 29, this value is sensitive to anisotropy. The Neel time constant increases exponentially with the cube of diameter, so for our 40 nm core particles, Brownian relaxation will dominate.…”
Section: Resultsmentioning
confidence: 71%
“…For magnetite based particles, such as used here, this critical magnetic core diameter is around 20 nm, though as demonstrated in Ref. 29, this value is sensitive to anisotropy. The Neel time constant increases exponentially with the cube of diameter, so for our 40 nm core particles, Brownian relaxation will dominate.…”
Section: Resultsmentioning
confidence: 71%
“…They consist of superparamagnetic or ferromagnetic particles of nano-or micrometer size embedded in a crosslinked polymer matrix [6]. In this way, they combine the properties of ferrofluids and magnetorheological fluids [7][8][9][10][11][12][13][14][15][16] with those of conventional polymers and rubbers [17]: we obtain elastic solids, the shape and mechanical properties of which can be changed reversibly from outside by applying external magnetic fields [6,[18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Comparing with magnetoviscosity measurements of Poiseuille flow of a magnetic fluid in a stationary cylinder with weakly nonequilibrium states, Patel et al 17 showed that the MRSh model could be in good agreement with their experimental results and that the Feld model may lead to significant disagreement with experiment. Comparing with transverse magnetization measurements of a magnetic fluid in a rotating cylinder (a rotating magnetic fluid) for a wide range of nonequilibrium state with a small magnetic field strength, Embs et al 18 showed with amplitude correction factors that the weak-field ML model with proper coefficient setting must be preferred. On the basis of a more exact insight into the hydrodynamic problem of rotating ferrofluids, Weng and In the next two sections, we first give an overview on the continuum theory of magnetic fluids and then test the six well-known models via comparisons with magnetoviscosity measurements, so as to make clear the magnetization relaxation due to the rotation of magnetic particles and to see how well these models make predictions on the basis of numerical calculations.…”
Section: Argument About Model Equationsmentioning
confidence: 99%